Analysis of the Influence of Tourism Education Promotion Program on the Decision to Choose Higher Education Polytechnic, Bintan Cakrawala-Lagoi - Prasiwi Citra Resmi; Muhammad Irsyad Atthaariq (Green Publisher Indonesia, 2021)
The purpose of this study was designed to determine the level of influence of the 6 elements of promotion on the decision to choose Bintan Cakrawala Polytechnic, Lagoi. This study uses a quantitative approach with descriptive analysis techniques. The population in this study used all Diploma-4 and Diploma-3 students at the Bintan Cakrawala Polytechnic Campus in the First and Second Academic Years. Data were collected using a Likert scale questionnaire. The results showed that there was an influence on the decision to choose a university (y) through advertising regression with the number of Tcount > T table (2.838 > 2.056) and a significant effect because the value of the Advertising variable T < 0.050. Direct Sales with the number of Tcount > Ttable (2,961 > 2.056) and has a significant effect because the value of the Direct Sales variable T < 0.050. And Interactive Media with the number of Tcount > Ttable (2.643 > 2.056) and a significant effect because the value of the Interactive Media T variable < 0.050 explained in the regression test results, 6 Promotion Elements simultaneously have a significant effect because the value of the F-Test variable < 0.050.